Changes of perceived control after kidney transplantation: a prospective study. (1st March 2017) - Schulz, Torben; Niesing, Jan; Homan van der Heide, Jaap J.; Westerhuis, Ralf; Ploeg, Rutger J.; Ranchor, Adelita V.
Abstract: Aims: The aim of this study was to determine if kidney transplantation is associated with increases of perceived control and how changes of perceived control affect the course of psychological distress until 1 year after transplantation. Background: Low levels of perceived control are associated with reduced well‐being among dialysis patients. Design: Prospective longitudinal cohort study. Methods: Perceived control (Mastery Scale) and psychological distress (GHQ‐12) were prospectively assessed before (T0; n = 470) and three (T1; n = 197), six (T2; n = 210) and twelve (T3; n = 183) months after transplantation. Differences between T1 and T0 perceived control were used to stratify the sample into three groups (control gain, stable control and control loss). Socio‐demographic and clinical variables, including complications, were examined as potential correlates and the course of psychological was distress compared across groups. Data were collected between July 2008 ‐ July 2013. Results: Perceived control showed a small increase overall, with 35·1%, 50·0% and 14·9% reporting gain, stable level and loss respectively. Patients with secondary schooling were overrepresented in the control loss group. The course of psychological distress varied across perceived control change groups, with patients in the control gain group experiencing a significant reduction in psychological distress. Conclusion: A considerable number of patients report increased levels of perceived control after transplantation that are associated with a subsequent decrease in psychological distress. Results emphasize the importance of perceived control and could inform interventions to facilitate well‐being after kidney transplantation.